The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00204-021-03093-1
|View full text |Cite
|
Sign up to set email alerts
|

Human metabolism and kinetics of the UV absorber 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328) after oral administration

Abstract: Abstract2-(2H-Benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328; CAS: 25973-55-1) is an ultraviolet light (UV) absorber which belongs to the class of hydroxy phenol benzotriazoles. Therefore, UV 328 is added to plastics and other polymers due to its photostability to prevent discoloration and prolong product stability which may result in an exposure of consumers. However, information about the toxic effects on humans and the human metabolism are still lacking. In the present study, human metabolism pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…The mass fraction of UV-328 in textiles should not be >0.1% according to Oeko-Tex . Previous studies have reported that UV-328, UV-329, UV-9, and UV-326 were seldom detected in textiles or in plastics in China. , In a kinetics study involving oral exposure to UV-328, the UV-328 excretion rate in urine was quite low and the UV-328 concentration was much higher in serum than urine . UV-328 may have a similarly low excretion rate in human breast milk.…”
Section: Resultsmentioning
confidence: 92%
“…The mass fraction of UV-328 in textiles should not be >0.1% according to Oeko-Tex . Previous studies have reported that UV-328, UV-329, UV-9, and UV-326 were seldom detected in textiles or in plastics in China. , In a kinetics study involving oral exposure to UV-328, the UV-328 excretion rate in urine was quite low and the UV-328 concentration was much higher in serum than urine . UV-328 may have a similarly low excretion rate in human breast milk.…”
Section: Resultsmentioning
confidence: 92%
“…The high concentrations found for bisphenol A and nonylphenol therefore do not result from bioaccumulation but from high exposure levels. This is different for substances such as UV-328 that are only slowly metabolized [21,22]. Experimental results show here that leaching into digestive fluids of seabirds is a relevant exposure pathway [17,18].…”
Section: ) View On Leaching Of Plastic Additives Too Narrowmentioning
confidence: 89%
“…For example, propyl paraben reached maximum serum levels 1.4 ± 1.1 h after oral administration (Shin et al 2019) and the natural product N,N-dimethyltyramine reached plasma peak levels 30-90 min after oral administration (Sommer et al 2020). Nevertheless, the structurally related BUVS 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV-328) showed retarded resorption kinetics as well and reached maximum blood levels 8 h after oral administration (Denghel et al 2021). The comparable findings for UV-327 and UV-328 indicate similar resorption processes for these substituted BUVSs.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the substance must, therefore, be excreted via an alternative route. Consistently, biliary excretion was assumed to be the main route of excretion for UV-328, too (Denghel et al 2021).…”
Section: Discussionmentioning
confidence: 99%